Passive immunization against Pseudomonas aeruginosa recombinant PilA in a murine burn wound model. (December 2016) - Mousavi, Mehdi; Behrouz, Bahador; Irajian, Gholamreza; Mahdavi, Mehdi; Korpi, Fatemeh; Motamedifar, Mohammad
Abstract: Pseudomonas aeruginosa type IV pili have an essential role in twitching motility, colonization and biofilm formation. In this study, we investigated the efficacy of intraperitoneal administration of rabbit anti-recombinant PilA (anti-r-PilA) immunoglobulin G (IgG) against P. aeruginosa infection in a mouse burn-wound model. After burn and infection, mortality rate was assessed in all mice, and that of mice passively immunized with rabbit anti-r-PilA IgG was compared to non-immunized mice. Bacterial quantities in the skin and internal organs were measured to determine the level of systemic infection. Results showed that passive immunotherapy with anti-r-PilA IgG protected the burned mice infected with P. aeruginosa strains, PAO1 and the clinical isolate (CI). Anti-r-PilA antibodies enhanced the opsonophagocytosis of these strains. Moreover, the administration of anti-r-PilA IgG was also successful in reducing the bacterial burden in infected mice. The reduction of systemic bacterial spread increased the survival rate of passively immunized mice. Findings of this study revealed an improved survival rate of 62.5%, thus confirming the protective effect of anti-r-PilA IgG. Highlights: Antibodies raised to recombinant PilA act as good opsonin for killing of P. aeruginosa strains. Antibodies raised to recombinant PilA can improve survival rate of mice with wound infection. The first report of protection against P. aeruginosa infection by antibodies against recombinant PilA.